Sektor Pariwisata terhadap Pembangunan Daerah di Kabupaten Lumajang - Cahyo, Herman Diartho (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
This research is a Descriptive research which aims to find out how much the level of labor elasticity of tourism subsector in Lumajnag regency, to know contribution of tourism subsector to local revenue (PAD) in Lumajang Regency, and to know the growth of labor absorption in tourism sector in Lumajang regency. The type of data used in this research is secondary data in the form of time series data with the object of research on the tourism subsector in Lumajang District and data obtained from the Department of Tourism, Department of Manpower and Dinas revenue Lumajang District in 2011-2017. Data analysis method used in this research is elasticity and proportion analysis. The results of this study indicate that the ability of the tourism subsector is not much in the absorption of labor that is equal to -1.49 percent of the number of workers who have worked or categorized as inelastic. In addition, the tourism subsector also did not contribute a considerable amount during the period of 2011-2017 to the Regional Original Income of Lumajang Regency which averaged only 1.41 percent. Overall contribution or contribution given by the tourism sector from year to year during the period 2011-2017 tends to decrease.